How to choose what to speak? Language practices in Malay-Chinese families in Singapore - Tan, Jo Mei Jing (2019)
Studies on language shift (LS) and language maintenance (LM) in Singapore have usually focused on the trends of individual ethnic communities’ vernaculars and English (Li, Saravanan & Ng, 1997; Vaish, 2007). However, with the phenomenon of increasing interethnic marriages, it is important to consider the possible effects of exogamous marriages on LS and LM. Exogamous marriages, particularly Malay-Chinese families, will be the focus of this thesis which aims to study interethnic families’ language practices and how Family Language Policy (FLP) in these families are negotiated. Through interviews and questionnaires with 16 Malay- Chinese interethnic families, this study found that English transcends both Malay and Mandarin in terms of language use in all domains. The languages participants use when conversing is also dependent on their interlocutors. Parental ideologies, both overt and covert, were revealed through the choice of their children’s Mother Tongue Language where the decision of Mandarin was justified by Mandarin’s importance for their children’s future while Malay was due to Chinese parents’ poor Mandarin proficiency. This paper also highlights the influence government policies have on Singaporeans’ perceptions on the statuses of languages. These language practices and choices may contribute to the present LS in Singapore, which is later argued in this thesis.